1998
DOI: 10.3109/02656739809018229
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Intracavitary Hyperthermia Combined with Radiation in the Treatment of Oesophageal Carcinoma

Abstract: Twenty-five patients with primary squamous cell carcinoma of the oesophagus were treated with intracavitary hyperthermia combined with external beam radiation and intraluminal radiation at Nanjing Jinling Hospital, China. External beam radiation was given with a 6-MV X-ray; 1.8-2.0 Gy per fraction and five fractions per week; this brought the total dose to 60 Gy. Two weeks later, hyperthermia was applied with 915 MHz microwave intracavitary applicators, which were designed at the City of Hope. Temperature meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Hishikawa et al 14 have reported a local control rate of 63% using external radiotherapy and brachytherapy. Mohanty et al 30 reported 44% local failures, whereas Ren et al 37 have reported 56% local failures in their series using external radiotherapy followed by ILRT and hyperthermia. Twenty patients (20%) developed local failure in our series within two treatment groups.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Hishikawa et al 14 have reported a local control rate of 63% using external radiotherapy and brachytherapy. Mohanty et al 30 reported 44% local failures, whereas Ren et al 37 have reported 56% local failures in their series using external radiotherapy followed by ILRT and hyperthermia. Twenty patients (20%) developed local failure in our series within two treatment groups.…”
Section: Discussioncontrasting
confidence: 59%
“…In our series, 16 patients (16%) developed strictures, with a significant correlation with dose of intraluminal brachytherapy. Ren et al 37 reported only mild esophageal fibrosis in one out of 25 patients treated using external beam radiation and intraluminal radiation in conjunction with hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 16 patients (16%) developed strictures, with a signi®cant correlation with dose of intraluminal brachytherapy. Ren et al 37 reported only mild esophageal ®brosis in one out of 25 patients treated using external beam radiation and intraluminal radiation in conjunction with hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Intracavitary hyperthermia may be a better way to selectively heat the tumor than external hyperthermia. Various applicators and application techniques for the clinical application of intracavitary hyperthermia have been reported [19][20][21][22][23][24] and it was concluded that intracavitary hyperthermia could improve local control.…”
Section: Discussionmentioning
confidence: 99%